Emission Reduction Strategies of a Low-Carbon Supply Chain Considering Product Substitution and Government Subsidy - Zhan, Menglin; Chen, Yan; Liu, Yue (Frontiers in Environmental Science, 2022)
Under the background of low carbon economy, consider that manufacturers produce common products and low-carbon products simultaneously and the two products are substituting, three models are set up, namely, no government subsidy, subsidy based on the research and development (R&D) cost and subsidy based on the production volume of low-carbon products. The Stackelberg game theory is used to analyze the optimal decision of supply chain under the three methods of government subsidy, the influence of correlation coefficient on optimal decision making is discussed, and the effects of different government subsidy methods on the equilibrium solutions are compared and analyzed. Finally, the results are verified and illustrated by example analysis. The study found that the government subsidy reduces the sales volume of common products, but increases the sales volume of low-carbon products, the emission reduction of unit low-carbon product, total emission reductions and manufacture’s profit. The unit emission reduction and total emission reductions are the highest when the government subsidies according to the R&D cost, and the manufacture’s profit is the highest when the government subsidies according to the production volume of low-carbon products. Total Emission reduction and supply members’ profit have a positive relationship with subsidy coefficient and the sensitivity of consumers toward price difference, and have a negative relationship with R&D cost coefficient.